First rainforest book - de la Bedoyere, Camilla; Elissambura (Essex, UK Miles Kelly, 2022)
Take a hike through some truly special forest habitats, and meet the animals that call them home. Each page is packed with amazing information, and the poster provides a colourful guide to the layers of the forest
Includes a forest layers poster
Science (Nature)
Keywords: Nature